The political origins of the Antarctic Treaty - Bulkeley, Rip (Polar Record, 2009)
Like many great institutions, the Antarctic Treaty system has its own creation myth, according to which it was brought into being by the Antarctic science programme of the 1957–1958 International Geophysical Year (IGY). As myths are prone to do, this one combines both an important truth and a good deal of misinformation. After fifty years in which it has shamelessly flattered the earth scientists, who are understandably rather fond of it, and undervalued the many non-scientists who advocated the internationalisation of Antarctica from 1910 onwards, it is time to lay it to rest. But before summarising the intermeshing contributions of private citizens, diplomats and other officials, and scientists, we should first take note of a different factor altogether, political geography.